Induced chlorophyll and viable mutations in Lablab purpureus (L.) sweet VAR. Typicus through gamma rays and ethyl methane sulphonate - S. MONICA,; N. SEETHARAMAN, (International Journal of Pharma and Bio Sciences, 2017)
Induced mutagenesis has become an effective tool to improve a crop through creation of variability. The present study was carried out to induce mutagenesis with CO(Gb)14 variety of Lablab purpureus (L.) Sweet var. typicus. The seeds of this variety were exposed to different doses/concentrations of gamma rays and Ethyl Methane Sulphonate . The mutagenic treated seeds were sown in the M1 field with control and harvested in bulk to raise M2 generation to observe the characters and number of mutants in each population. A wide range of chlorophyll and morphological mutants were observed in the M2 generations. The chlorophyll mutants identified in the treated population were albino, xantha, chlorina and viridis. The morphological mutation consisted of tall, dwarf, bushy, tendrillar, unifoliate leaf, bifoliate leaf, tetrafoliate leaf, wrinkled leaf, narrow rugose leaf, biforked leaf, triforked leaf, extra standard petal, extra wing petal, early maturity, late maturity, single seed pod and long pod. EMS induced higher proportion of chlorophyll and viable mutants than gamma rays and the highest mutation frequency was induced in 30mM of EMS followed by 25KR of gamma rays. The frequency of these mutations is agronomically desirable which may be utilized in the development of new cultivar.